Предмет: Алгебра,
автор: viktoriaryassomaha
решить уравнение пожалуйста
х•(х-2)•(х+1)=х2°(х-1)
Ответы
Автор ответа:
0
x (x - 2)(x + 1) = x2(x-1)
(x²+ 2x)(x + 1) = x2(x - 1)
(x²+ 2x)(x + 1) = 2x(x - 1)
x³+ x²+ 2x²+ 2x = 2x(x-1)
x³+ x²+ 2x²+ 2x = 2x²-2x
x³+ x²+ 2x = - 2x
x³+x²+2x + 2x = 0
x³+x²+ 4x = 0
x(x²+x + 4) = 0
x² + x + 4 = 0
x = 0
Похожие вопросы
Предмет: Математика,
автор: polinagontova9
Предмет: Алгебра,
автор: helgesander28
Предмет: Химия,
автор: Cheburashka222
Предмет: Английский язык,
автор: Света3811
Предмет: Математика,
автор: Mariia2543